Peran Kepemimpinan Kepala Sekolah Dalam Meningkatkan Mutu SMA Kartika X-1 Jakarta Selatan - Sidabutar, Janpristiwandi; Warta, Waska; Suryadi, Toto; Sukamto (AL MURABBI, 2023)
This study discusses the role of school principals as managers in improving the quality of education, principals as leaders in improving the quality of education, supporting and inhibiting factors, as well as solutions to facing inhibiting factors in improving the quality of education. In this study the authors used a qualitative research method, namely a method based on the philosophy of postpositivism, used to examine natural object conditions, where the researcher was the key instrument, purposive sampling of data sources, collection techniques by triangulation (combined), analysis the data are inductive/qualitative in nature and the results of qualitative research emphasize meaning rather than generalization. This type of research is field research and library research. Using primary data and secondary data, qualitative research instruments with data collection techniques Primary data obtained from interviews with SMAS KARTIKA X_1 South Jakarta and filling out questionnaires with the relevant informants are collected and processed in advance to simplify the data. The results of this study are that the principal has a major role in improving the quality of SMA. With a clear vision, effective pedagogical leadership, good resource management, collaboration with stakeholders, coaching and staff development, as well as comprehensive monitoring and evaluation, school principals can bring about significant changes in improving the quality of education at SMA Kartika X-1 Jakarta South.